Protein substitutions as new-generation pharmanutrition approach to managing phenylketonuria - Fatma Nur Keskin; Teslime Özge Şahin; Raffaele Capasso; Duygu Ağagündüz (The Korean Pediatric Society, 2023)
Phenylketonuria (PKU), an autosomal recessive inherited metabolic disorder, is caused by a mutation in the phenylalanine hydroxylase (PAH) gene on the 12th chromosome. Defective PAH activity ultimately leads to increased phenylalanine (Phe) blood concentrations (hyperphenylalaninemia) that harm the brain. The primary purpose of PKU treatment is to maintain the blood Phe level to prevent certain undesired effects. Hence, lifelong medical nutrition therapy is recommended for these patients. The usefulness of natural protein sources may be limited, as they are based on individual Phe tolerance, and a patient's daily protein requirements are supported by Phe-free amino acid mixtures. A few PKU treatment centers recently started using supplemental casein glycomacropeptide, pegvaliase, or large neutral amino acids, and some patients are treated by responding to tetrahydrobiopterin, which works as a pharmaceutical chaperone (prescribed as sapropterin dihydrochloride). This review discusses the efficacy and safety considerations of basic medical nutrition approaches and newgeneration protein substitutes that are used to treat PKU.